Do the Migrant Workers’ Remittances foster Economic Growth in the South Asian Countries? A Panel Analysis - Akter, Arjina; Ale, Sonia Afrin; Islam, Sheikh Monjurul (International Journal of Economics and Financial Issues, 2024)
The purpose of this study is to investigate the effect of migrant workers’ remittances on economic growth in South Asian countries using panel data from 1980 to 2020, resulting in 123 observations. I consider here the top three remittance-receiving countries in South Asia, namely Bangladesh, India, and Pakistan. The growth model is estimated using pooled ordinary least squares (OLS), fixed-effects, and random-effects approaches. The empirical results did not support the hypothesis and it indicates that migrant workers’ remittances inflow growth does not lead to growth in the three South Asian countries based on the fixed-effects method since the random-effects model is rejected in statistical tests. The analysis suggests that a 1% increase in growth of remittance inflows decreases the economic growth by approximately 1.1%, and a 1% increase in foreign direct investment inflow decreases the economic growth of sample countries by roughly 0.14%. The regression results also indicate a positive impact of trade openness on economic growth. Additionally, the study shows no significant relationship between inflation and economic progress.